EVALUTION OF THE SINGLE INTERCITY FREIGHT TRANSPORTATION WAITING TIME - Ponomariova, N.; Makarichev, А.; Mospan, N.; Пономарева, Н. В.; Макаричев, А. В.; Мосьпан, Н. В.; Пономарьова, Н. В.; Макарічев, А. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The example of vechicle operation on the pendulum intercity route during single freightages processing is considered. Two approaches to the definition of the single freightage waiting time by the carrier are proposed. These approaches allow to take into account the probability of the single freightage obtaining by the carrier during the different load level of the transport enterprise capacity.
ОЦЕНКА ВРЕМЕНИ ОЖИДАНИЯ РАЗОВЫХ ЗАЯВОК НА ПЕРЕВОЗКУ ГРУЗОВ В МЕЖДУГОРОДНОМ СООБЩЕНИИ
ОЦІНКА ЧАСУ ОЧІКУВАННЯ РАЗОВИХ ЗАМОВЛЕНЬ НА ПЕРЕВЕЗЕННЯ ВАНТАЖІВ У МІЖМІСЬКОМУ СПОЛУЧЕННІ
Keywords: single freightage; intercity freight transportation; waiting time; freight flow; разовая заявка; перевозка грузов в междугородном сообщении; время ожидания; поток заявок; разове замовлення; перевезення вантажів у міжміському сполученні; час очікування; потік замовлень; 656.[95+136]